Electricity externalities, siting, and the energy mix: A survey - Heinz Welsch (University of Oldenburg, Department of Economics, 2016)
While early literature on electricity externalities was largely concerned with fossil fuel power generation and the associated emissions, nuclear accidents (Chernobyl, Fukushima) and the large-scale deployment of renewable energy facilities have spurred a wave of research on the externalities of nuclear power and renewable energies. The issue is important because many countries have started reconsidering their energy policies, and the externalities from electricity generation play a major role in the benefit-cost analysis of relevant options. This paper reviews the literature on electricity-related externalities. It starts by discussing their nature and the methods employed in valuing them. It finds that appraisals of electricity externalities are complicated because of heterogeneity of both the externalities themselves and the methods applied in measuring them. The paper reviews valuation studies of the externalities from fossil fuel, nuclear and renewable sources, and it discusses the relevance of their findings for the siting of plants and the electricity mix. It concludes by pointing out gaps in our knowledge about electricity externalities that deserve to be addressed in future research.
Keywords: Q48; Q42; Q51; Q53; Q54; 330; electricity generation; externalities; fossil fuels; nuclear power; renewable energy; siting; electricity mix; property value; willingness to pay; subjective well-being